Studi Tafsir Ayat Martabat Manusia Dalam QS. Al-Hujurat: 11, Upaya Preventif Tindakan Bullying - Khairunnisa Bakri; Abrar M Dawud Faza (Universitas Cokroaminoto Yogyakarta, 2025)
This qualitative-descriptive and thematic interpretation research through literature study aims to examine the values of human dignity in QS. Al-Hujurat [49]: 11 as a preventive effort against increasingly complex bullying acts in the contemporary social context. Four main ethical principles in the verse can be integrated into bullying prevention strategies: verbal prohibition (sukhriyyah), symbolic prohibition (lamz), avoidance of giving bad nicknames (alqab), and a call to repentance as moral correction. Its contribution is significant to the formation of social ethics, character education, and strengthening child protection policies. The study recommends the integration of Qur'anic values in the anti-bullying curriculum and the formation of a culture of mutual respect in physical and digital spaces. Further research to explore the implementative dimensions of this verse through a participatory and interdisciplinary approach.